Globalization and Sustainability Recent Advances, New Perspectives and Emerging Issues - Mori, Margherita (Sustainable Development, 2022)
The debate on globalization and sustainability has gained momentum in the last few years, thus shedding light on the interrelatedness of these two concepts as well as on their cross-cultural aspects. The 2030 United Nations Agenda adopted in 2015 is a shared blueprint for partnerships for peace and prosperity for people and the planet. This strategic to-do list involves meeting Sustainable Development Goals and associated targets linked to sustainable growth, tourism and food systems, reduced energy and water costs, improved health, and increased productivity. This book is centered upon these fields of knowledge and discusses recent advances, new perspectives, and emerging issues. Its ultimate objective is to provide a comprehensive overview of related multi-faceted dimensions while bridging the gap between theory and practice. Chapters in this volume cover a wide array of areas of research pertaining to the never-ending and unlimited expanding of both international economies and operations, embedding excellence and sustainability into business strategic objectives, and rethinking an approach to sustainable globalization. Special attention is paid to financial implications, due to the key role that finance plays to complement the real sphere of the economy and that has increasingly attracted the attention of both academics and practitioners.